Genome-resolved metagenomic analysis of a conserved spirochete symbiont in pyrroloiminoquinone producing sponges - Solomons, Gabriella Malaika (Rhodes University, 2026)
Symbiotic relationships between sponges and their associated bacteria represent one of the oldest examples of symbiosis on Earth. Bacterial symbionts are acquired by their sponge hosts for a number of reasons including the uptake of nutrients, acquisition of carbon, nitrogen and phosphorous, the recycling of waste and other metabolic byproducts, the production of amino acids, stabilizing of the host skeletal system and facilitating chemical defensive strategies against pathogens and predators through the production of bioactive secondary metabolites. Marine sponges of the Latrunculiidae family are the most prolific producers of the bioactive secondary metabolites known as pyrroloiminoquinones, a class of alkaloids with a broad spectrum of biological activities and considerable potential as future drug leads. The microbial communities associated with several genera within this family of sponges are highly conserved and dominated by two bacterial symbionts – a broad-host range Tethybacterales symbiont and a Spirochete symbiont, exclusive to sponges of the Tsitsikamma genus and Cyclacanthia bellae species. Dominant spirochete communities have only been reported in the microbiomes of Clathrina clathrus sponges, where they play a role in calcification of the sponge skeletal tissue. This study was aimed at investigating the nature of the symbiotic relationship between latrunculid sponges and their conserved spirochete symbiont with respect to the production of pyrroloiminoquinones. These spirochetes were shown to be newly acquired symbionts that are currently undergoing genome reduction and are distinct from other sponge-associated spirochetes. Assessment of the functional potential of these spirochetes suggested that these symbionts were selected by their sponge hosts due to their ability to produce terpenoids and may provide antioxidizing effects to the sponge.
Keywords: Uncatalogued